2007
DOI: 10.1002/adsc.200600651
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium and Iridium Nanoparticles Entrapped in Aluminum Oxyhydroxide Nanofibers: Catalysts for Hydrogenations of Arenes and Ketones at Room Temperature with Hydrogen Balloon

Abstract: Abstract:The recyclable metal nanoparticle catalysts, rhodium in aluminum oxyhydroxide [Rh/ AlO(OH)] and iridium in aluminum oxyhydroxide [Ir/AlO(OH)], were simply prepared from readily available reagents. The catalysts showed high activities in the hydrogenation of various arenes and ketones under mild conditions. Selective hydrogenation was possible for bicyclic and tricyclic arenes in high yields. The catalysts were active at room temperature even with a hydrogen balloon. Also, the catalysts showed high tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(46 citation statements)
references
References 60 publications
1
44
0
1
Order By: Relevance
“…Clearly, their morphologies affect not only the catalytic reactivity, but also the catalytic selectivity [15]. Thus, the issues of controlling their size and shape were considered in catalysis [1] and the structure sensitivity to a larger surface area [16,17]. Here, an effort is made to prepare cubic and octahedral Rh nanoparticles by polyol method using AgNO 3 and RhCl 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, their morphologies affect not only the catalytic reactivity, but also the catalytic selectivity [15]. Thus, the issues of controlling their size and shape were considered in catalysis [1] and the structure sensitivity to a larger surface area [16,17]. Here, an effort is made to prepare cubic and octahedral Rh nanoparticles by polyol method using AgNO 3 and RhCl 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Catalytically active supported metallic Rh nanoparticles have mostly been employed in hydrogenations including the reduction of 1-alkenes, [174] arenes, [45b, 175] and ketones [175] (Figure 26), CO hydrogenation, [176] and in the reduction of various a,b-unsaturated compounds. [177,178] Savastenko et al reported the lean NO x reduction using supported metallic Rh nanoparticles on SiO 2 in the 100-400 8C temperature range and employing a representative test gas mixture of oxygen-rich diesel engine exhaust gas.…”
Section: Platinummentioning
confidence: 99%
“…TEM images and particle size distribution of Rh metal nanoparticles on aluminum oxyhydroxide nanofibers, used in the hydrogenation of arenes at room temperature with a hydrogen balloon. [175] Reproduced with permission. Figure 25.…”
mentioning
confidence: 97%
“…[1] Boron-and aluminum-based hydride reagents have been widely used for the reduction of ketones to secondary alcohols, but such methods require the use of more than stoichiometric amounts of reductants and generate vast amounts of inorganic waste. [2] Improved methods using recyclable Ir nanoparticles [4] under 0.4 MPa of H 2 at 75 8C or Rh nanoparticles [5] under atmospheric H 2 pressure at room temperature have recently been reported. Hydrogenation using heterogeneous catalysts possessing a transition metal, such as Ru, Rh, Pd, and Pt, has been used for both the industrial and laboratory scale reduction of ketones because of the advantages of easy separation from the reaction mixture, recyclability, and low cost performance.…”
Section: Introductionmentioning
confidence: 99%
“…Aliphatic ketones are quite stable under the hydrogenation conditions, and the reduction often requires strong conditions, such as acid or base treatment, elevated temperature and/or high H 2 pressure, to obtain the hydrogenated secondary alcohols. [2] Improved methods using recyclable Ir nanoparticles [4] under 0.4 MPa of H 2 at 75 8C or Rh nanoparticles [5] under atmospheric H 2 pressure at room temperature have recently been reported. The use of supported silica heterogeneous catalysts, such as Ru-Sn-B/SiO 2 , [6] Si-S-Pt, [7] and silica-SMAP-[Rh(cod)(OMe)] [8] (SMAP = silicon-constrained monodentate trialkylphosphine, COD = 1,5-cyclooctadiene, OMe = methoxy), as well as sodium hydride containing a nickel salt [NaH-NaOtAm-Ni(OAc) 2 ] (NaOtAm = sodium 2-methyl-2-butoxide, OAc = acetate), [9] afforded an efficient hydrogenation under atmospheric H 2 pressure at room temperature.…”
Section: Introductionmentioning
confidence: 99%